Insights into the role of TLR21 in innate immunity of Japanese flounder (Paralichthys olivaceus) - Yuting Song; Yuanxin Yang; Shuo Zhang; Songlin Chen; Guobin Hu (Fish & Shellfish Immunology, 2026)

Ferritin-mediated copper delivery induces dual cell death across diverse leukemia types - Huaiji Wang; Wenjing Wang; Wenqiang Sun; Feifan Liu; Caopei Zheng; Xiaoyun Lin; Yuhua Li; Weier Bao; Xiaoming Hu; Guobin Qi; Feng Li; Guanghui Ma; et al. (Science Bulletin, 2026)

Zeolite-enhanced intermittent aeration for stabilizing aerobic granular sludge under low organic loading: Process performance and mechanisms - Yuanyuan Lu; Yongyou Hu; Donghui Liang; Xiaoqiang Zhu; Guobin Wang; Jieyun Xie (Journal of Water Process Engineering, 2026)

Time-Series Transcriptomics of a Gill Cell Line (BTG) from Chinese Bahaba (Bahaba taipingensis) During ISKNV Infection (3–24 hpi) - Chenfei Guo; Zhihong Gong; Fei Fang; Xihong Li; Lei Wang; Na Wang; Zhangfan Chen; Lin Yan; Kuoqiu Yan; Guobin Hu; Songlin Chen (Fishes, 2026)
The Chinese bahaba (Bahaba taipingensis), an endangered marine fish, is highly vulnerable to infectious spleen and kidney necrosis virus (ISKNV). In this work, we developed a gill filament-derived cell line, designated BTG, to investigate how these cells respond to ISKNV over time, specifically from 3 to 24 h post-infection (hpi). BTG cells grew steadily, displayed a diploid chromosome number of 2n = 48, demonstrated high transfection efficiency, and were highly susceptible to viral infection. Characteristic cytopathic effects (CPEs) became noticeable as early as 6 hpi at 27 °C. RNA-seq profiling showed that the number of differentially expressed genes (DEGs) steadily increased with time. Standard enrichment analysis at individual time points (3, 6, 12, and 24 hpi) highlighted pathways mainly involved in DNA replication, cell cycle control, ribosome assembly, transcription and translation, mismatch repair, and cell adhesion. Temporal clustering analysis, however, revealed hidden patterns in immune gene expression. Genes that were consistently downregulated were enriched in immune-related pathways, including ECM–receptor interaction, cytokine–receptor signaling, PI3K–AKT, and Wnt signaling, indicating prolonged suppression of host defense mechanisms. In contrast, clusters of genes transiently upregulated during the first 6 h post-infection were associated with antiviral and innate immune pathways, such as NF-κB, JNK, IRF3, IRF7, caspases, JAK, MHC I, and lysosome-related functions, suggesting a rapid but short-lived antiviral response. Genes that were continuously upregulated were primarily involved in nucleic acid replication and protein synthesis, reflecting a gradual host cell reprogramming to support viral replication. Taken together, these findings reveal a temporal shift in BTG cells from an initial burst of immune activity to immune suppression, accompanied by enhanced viral replication. The BTG cell line thus represents a valuable in vitro model for dissecting ISKNV–host interactions and offers new perspectives on the molecular strategies employed by megalocytiviruses in B. taipingensis.

De novo establishment of a stable brain cell line from Cephalopholis sonnerati (tomato grouper) and transcriptomic dissection of its response to nervous necrosis virus (NNV) infection - Zhihong Gong; Fei Fang; Xiaoli Guo; Chenfei Guo; Na Wang; Lei Wang; Chongwei Wang; Guobin Hu; Bo Zhou; Songlin Chen (Fish & Shellfish Immunology, 2026)

Reprogramming the intrinsic capsular polysaccharide biosynthesis pathway for efficient secretory production of chondroitin in Escherichia coli Nissle 1917 - Shan Hu; Siyan Zhou; Mingming Zheng; Haibo Xiong; Guobin Yin; Fengling Yang; Ping Dong; Jian Chen; Ruirui Xu; Zhen Kang (Chemical Engineering Journal, 2026)

The role of particle shape irregularity in the constitutive behavior of aeolian dune sand: Insights from DEM simulations - Minyi Zhu; Shiva Prashanth Kumar Kodicherla; Guobin Gong; Kai Li; Naveen Revanna; Hu Zheng (Bulletin of Engineering Geology and the Environment, 2026)

Effects of polystyrene nanoplastics on tomato plant growth, fruit yield and quality - Mingyuan You; Ting Zhou; Jiahui Yan; Jingyue Ma; Tingting Kong; Songshen Hu; Guobin Li; Xiaohui Hu; Xiaojing Li (Food Chemistry, 2026)

SlNAC63-SlbHLH71 module enhances tomato saline-alkali tolerance via regulating JA biosynthesis and ROS scavenging - Xiangguang Meng; Zhen Kang; Xiaoyan Liu; Qingpeng Li; Zhenglun Li; Zihan Chu; Songshen Hu; Zhi Zhang; Guobin Li; Tianlai Li; Xiaohui Hu (Theoretical and Applied Genetics, 2026)

Characterization of TLR14 ligands, adaptor proteins and immune mechanisms in Japanese flounder (Paralichthys olivaceus) - Yuting Song; Zhihong Gong; Songlin Chen; Guobin Hu (Fish & Shellfish Immunology, 2025)

Efficient degradation of diclofenac by FeS2-Cu2S activated peroxymonosulfate: Performance and mechanism - Chaoyang Tang; Jingyu Liu; Yongyou Hu; Yan Liu; Yueyue Shi; Jianhua Cheng; Xiaoqiang Zhu; Guobin Wang; Jieyun Xie (Journal of Cleaner Production, 2025)

Stable and efficient n-type perylene diimides radical as cathode interlayer with wide thickness tolerance for organic solar cells - Lin Hu; Senmei Lan; Guobin Shen; Fang Wang; Yingzhi Jin; Zhen Su; Jia Yao; Mengzhen Du; Zheng Yan; Wei Li; Dan Zhou; Erjun Zhou; et al. (Chemical Engineering Journal, 2025)

Enhanced co-catalytic Fenton degradation of sulfamethoxazole by partitional reaction with H2O2 intermittent addition: From theoretical research to practical application - Chun Xiao; Jingyu Liu; Yongyou Hu; Chaoyang Tang; Jianhua Cheng; Yuancai Chen; Xiaoqiang Zhu; Guobin Wang; Jieyun Xie; Lihong Ai (Journal of Water Process Engineering, 2025)

Self-healing and thickness-insensitive perylene diimide-based cathode interfacial layers for organic solar cells - Wei Chen; Dan Zhou; Lin Hu; Jiangang Ma; Guobin Shen; Wentian Wan; Shuhua Wang; Fang Wang; Ruizhi Lv; Bin Hu; Haitao Xu; Zaifang Li; et al. (Chemical Engineering Journal, 2025)

Synergistic effects and mechanistic insights of zeolite-enhanced intermittent aeration in aerobic granular sludge formation - Yuanyuan Lu; Yongyou Hu; Donghui Liang; Xiaoqiang Zhu; Guobin Wang; Jieyun Xie (Journal of Water Process Engineering, 2025)

Inoculation with Acinetobacter indicus CZH-5 in internal circulation airlift zeolite spheres sequencing batch reactor to augment simultaneous removal of nitrogen, phosphorus, and tetracycline - Zuhao Chen; Yongyou Hu; Guanglei Qiu; Donghui Liang; Jianhua Cheng; Yuancai Chen; Guobin Wang; Xiaoqiang Zhu; Jieyun Xie (Journal of Hazardous Materials, 2025)

Establishment and characterization of a gill cell line from turbot (Scophthalmus maximus) - Jiaqi Wang; Xiang Shi; Zhihong Gong; Songlin Chen; Guobin Hu (Fish & Shellfish Immunology, 2025)

Unlocking the power of manganese-doped MoS2 hollow nanotubes: A game-changing Fenton co-catalyst for ciprofloxacin degradation - Jingyu Liu; Yongyou Hu; Xian Li; Yuming Liu; Yuancai Chen; Jianhua Cheng; Xiaoqiang Zhu; Guobin Wang; Jieyun Xie (Chemical Engineering Journal, 2025)

The light-responsive transcription factor SlBBX20 improves low-temperature resistance of Solanum lycopersicum by affecting photosynthetic capacity, antioxidant capacity, and osmotic adjustment - Yongbo Ma; Manling Chen; Yingjin Xing; Zhenglun Li; Ting Zhou; Haijing Yan; Jiahui Yan; Songshen Hu; Guobin Li; Xiaohui Hu; Xiaojing Li (Plant Cell Reports, 2025)

The effect of particle elongations on incremental behavior of granular materials using discrete element method - Minyi Zhu; Guobin Gong; Shiva Prashanth Kumar Kodicherla; Kai Li; Yu Huang; Hu Zheng (Computers and Geotechnics, 2025)

Performance and mechanisms of nitrogen removal from low-carbon source wastewater in an iron-carbon coupled biofilm airlift internal circulation sequencing batch reactor - Jing Ni; Yongyou Hu; Donghui Liang; Jianhua Cheng; Yuancai Chen; Xiaoqiang Zhu; Guobin Wang; Jieyun Xie (Bioresource Technology, 2025)

A novel bio-microcapsule with high mechanical strength for sustained release of carbon sources and iron ions to enhance nitrogen removal in low-carbon sewage - Zitian Mai; Yongyou Hu; Donghui Liang; Xiaoqiang Zhu; Guobin Wang; Jieyun Xie (Journal of Water Process Engineering, 2025)

Establishment and characterization of cell line from fin of Chinense bahaba (Bahaba taipingensis) and transcriptome analysis of its response to megalocytivirus SKIV-SD strain infection - Zhihong Gong; Qi Zhang; Na Wang; Lei Wang; Zhangfan Chen; Lin Yan; Kuoqiu Yan; Guobin Hu; Songlin Chen (Aquaculture, 2024)

MoS2 sponge co-catalytic Fenton reaction for efficient degradation of antibiotics: Performance, mechanism and reactor operation - Jingyu Liu; Yongyou Hu; Shangqing Ma; Chun Xiao; Yan Liu; Yuancai Chen; Jianhua Cheng; Xiaoqiang Zhu; Guobin Wang; Jieyun Xie (Journal of Water Process Engineering, 2024)

Fault diagnosis method of marine centrifugal fan based on adversarial network learning - Congyue Li; Guobin Li; Dexin Cui; Yihuai Hu (Ocean Engineering, 2024)

Unraveling the effects and mechanisms of antibiotics on aerobic simultaneous nitrogen and phosphorus removal by Acinetobacter indicus CZH-5 - Zuhao Chen; Yongyou Hu; Guanglei Qiu; Donghui Liang; Jianhua Cheng; Yuancai Chen; Xiaoqiang Zhu; Guobin Wang; Jieyun Xie (Journal of Hazardous Materials, 2024)

The digital twins for mine site rescue environment: Application framework and key technologies - Hu Wen; Shengkai Liu; Xuezhao Zheng; Guobin Cai; Bo Zhou; Wen Ding; Yizhuo Ma (Process Safety and Environmental Protection, 2024)

Coordinated optimization of the polymerization and transportation processes to enhance the yield of exopolysaccharide heparosan - Shan Hu; Siyan Zhou; Yang Wang; Wuxia Chen; Guobin Yin; Jian Chen; Guocheng Du; Zhen Kang (Carbohydrate Polymers, 2024)

Effective degradation of norfloxacin by 3D diatomite plate@polydopamine@WC co-catalytic Fenton at near-neutral pH - Yueyue Shi; Yongyou Hu; Yan Liu; Chaoyang Tang; Jianhua Cheng; Xiaoqiang Zhu; Guobin Wang; Jieyun Xie (Chemical Engineering Journal, 2024)

Genomics and metabolic characteristics of simultaneous heterotrophic nitrification aerobic denitrification and aerobic phosphorus removal by Acinetobacter indicus CZH-5 - Zuhao Chen; Yongyou Hu; Guanglei Qiu; Donghui Liang; Yiyong Li; Jianhua Cheng; Yuancai Chen; Guobin Wang; Jieyun Xie; Xiaoqiang Zhu (Bioresource Technology, 2024)

M6PR interacts with the HA2 subunit of influenza A virus to facilitate the fusion of viral and endosomal membranes - Yuzhen Hu; Li Jiang; Guangwen Wang; Yangming Song; Zhibo Shan; Xuyuan Wang; Guohua Deng; Jianzhong Shi; Guobin Tian; Xianying Zeng; Liling Liu; Hualan Chen; et al. (Science China Life Sciences, 2024)

Presence of a long nuclear-localization signal sequence in homeodomain transcription factor Nkx1.2 - Xinyi Li; Lihui Chen; Xinyuan Wang; Chen Sun; Guangdong Ji; Guobin Hu; Zhenhui Liu (Journal of Oceanology and Limnology, 2024)

Efficient degradation of ciprofloxacin by 3D oxygen-doped MoS2/polyacrylamide/graphene oxide composite hydrogel co-catalytic Fenton reaction - Yueyue Shi; Yongyou Hu; Jianhua Cheng; Xiaoqiang Zhu; Guobin Wang; Jieyun Xie (Journal of Environmental Chemical Engineering, 2024)

Exploring Acoustic Wave Propagation and Equivalent Path in Quasi-Porous Medium of Loose Coal Mass - Jun Guo; Changming Chen; Guobin Cai; Hu Wen; Shuai Li (Natural Resources Research, 2024)

Transcriptome analysis reveals immune-related genes in tissues of Vibrio anguillarum-infected turbot Scophthalmus maximus - Yuting Song; Maqsood Ahmed Soomro; Xianzhi Dong; Guobin Hu (Journal of Oceanology and Limnology, 2024)

Establishment and identification of a skin cell line from Chinese tongue sole (Cynoglossus semilaevis) and analysis of the changes in its transcriptome upon LPS stimulation - Zhihong Gong; Chenfei Guo; Jiacheng Wang; Songlin Chen; Guobin Hu (Fish & Shellfish Immunology, 2023)

Establishment, characterization and application in germplasm conservation and disease resistance: An embryonic cell line from Yangtze sturgeon (Acipenser dabryanus) - Zhihong Gong; Qi Zhang; Juanjuan Liu; Guobin Hu; Songlin Chen; Na Wang (Aquaculture, 2023)

High-efficient degradation of chloroquine phosphate by oxygen doping MoS2 co-catalytic Fenton reaction - Jingyu Liu; Yongyou Hu; Xian Li; Chun Xiao; Yueyue Shi; Yuancai Chen; Jianhua Cheng; Xiaoqiang Zhu; Guobin Wang; Jieyun Xie (Journal of Hazardous Materials, 2023)

Degradation of sulfamethoxazole by super-hydrophilic MoS2 sponge co-catalytic Fenton: Enhancing Fe2+/Fe3+ cycle and mass transfer - Chun Xiao; Yongyou Hu; Qitian Li; Jingyu Liu; Xian Li; Yueyue Shi; Yuancai Chen; Jianhua Cheng; Xiaoqiang Zhu; Guobin Wang; Jieyun Xie (Journal of Hazardous Materials, 2023)

Comprehensive evaluation on effect of planting and breeding waste composts on the yield, nutrient utilization, and soil environment of baby cabbage - Yali Qiao; Jianzhong Tie; Xuehua Wang; Baihong Wei; Wenbin Zhang; Zeci Liu; Guobin Zhang; Jian Lyu; Weibiao Liao; Linli Hu; Jihua Yu (Journal of Environmental Management, 2023)

Nitrogen removal performance and mechanism of low-carbon sewage by airlift internal loop sequencing batch bio-microcapsule reactor - Weiting Zhang; Yongyou Hu; Donghui Liang; Guobin Wang; Jieyun Xie; Xiaoqiang Zhu (Journal of Water Process Engineering, 2023)

Performance and mechanism of simultaneous nitrification and denitrification in zeolite spheres internal loop airlift reactor - Xiaojing Wen; Donghui Liang; Yongyou Hu; Xiaoqiang Zhu; Guobin Wang; Jieyun Xie (Bioresource Technology, 2023)

Transcriptome analysis of turbot ( Scophthalmus maximus ) head kidney and liver reveals immune mechanism in response to Vibrio anguillarum infection - Yuting Song; Xianzhi Dong; Guobin Hu (Journal of Fish Diseases, 2022)
The diseases triggered by Vibrio anguillarum infection have created huge economic losses to the turbot ( Scophthalmus maximus ) farming industry. However, the immune mechanism of turbot to V. anguillarum infection has not been deeply investigated. To better understand the immune response of turbot to V. anguillarum infection, transcriptome analysis of the head kidney and liver of turbot was performed. A total of 15,948 and 11,494 differentially expressed genes (DEGs) were obtained from the turbot head kidney and liver, respectively. Transcriptome analysis revealed that the head kidney and liver of turbot have some differences in the gene ontology and Kyoto Encyclopedia of Genes and Genomes enrichment analysis of the DEGs for the different functions of these two organs. Although there are many uncertain factors in this immune process, such as the occurrence of alternative splicing (AS) events and the differences in the protein structure of the DEGs, the NFκB signalling pathway, MKK‐dependent AP‐1 activation, JAK‐STAT signalling pathway, the signal transmission of MHC Ⅰ and a series of DEGs including HSP90 driving NLRP3 to produce inflammatory factors (IL‐1β, IL‐8, TNFα, etc.) were possible important immune response pathways for turbot to V. anguillarum infection. Overall, our research has conducted a preliminary exploration of the immune mechanism of turbot in response to V. anguillarum infection.

Appropriate Ammonium/Nitrate Mitigates Low Light Stress in Brassica pekinensis by Regulating the Nitrogen Metabolism and Expression Levels of Key Proteins - Linli Hu; Yue Wu; Mohammed Mujitaba Dawuda; Weibiao Liao; Jian Lv; Yutong Li; Jihua Yu; Jianming Xie; Zhi Feng; Guobin Zhang; Alejandro Calderón-Urrea (Journal of Plant Growth Regulation, 2021)

Spatial Heterogeneity of Marine Environment Changes: A Case Study in Laizhou Bay and Its Adjacent Waters, China - Youxiao Wang; Ge Yu; Guobin Hu; Dahai Liu (Journal of Ocean University of China, 2021)

Spatial variations in trophic-functional patterns of periphytic ciliates and indications to water quality in coastal waters of the Yellow Sea - Mohammad Nurul Azim Sikder; Mamun Abdullah Al; Guangjian Xu; Guobin Hu; Henglong Xu (Environmental Science and Pollution Research, 2019)

Recent changes in precipitation extremes in the Heihe River basin, Northwest China - Aifang Cheng; Qi Feng; Guobin Fu; Jiankai Zhang; Zongxing Li; Meng Hu; Gang Wang (Advances in Atmospheric Sciences, 2015)

Temporal variation of wind speed in China for 1961–2007 - Guobin Fu; Jingjie Yu; Yichi Zhang; Shanshan Hu; Rulin Ouyang; Wenbin Liu (Theoretical and Applied Climatology, 2011)

Differential display reveals a cDNA coding for an acyltransferase-like protein specific to taxol synthesis inTaxus chinensis - Guobin Hu; Xingguo Mei; Qianbin Xiong; Aiwen Zhou; Wei Gong (Plant Molecular Biology Reporter, 2002)